Points based systems and the Blue Card directive: concurrence and complementarity in the regulation of highly skilled migration in the European Union - Iglesias Sánchez, Sara (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2013)
The European Union has decided to get involved inthe global competition for highly skilled workers by adopting a new legal instrument: the Blue Card Directive. Nonetheless, two of the three Member states that do not participate in the application of the Directive have opted for a different approach, relying in the modelof the «points based systems» successfully applied by some third countries. The coexistence of alternative systems to attract qualified workers in the European migration arena poses several questions with regard to the effectiveness of both methods and to their effects in the construction of a common migration policy. After analyzing these issues, we will assess the extent to which the Directive offers a significant added value